Afroboletus sequestratus (Boletales), the first species with sequestrate basidioma in the genus - Han, Li-Hong; Buyck, Bart; Yorou, Nourou S.; Halling, Roy E.; Yang, Zhu L. (Phytotaxa, 2017)
A new species of Afroboletus, namely A. sequestratus, is described from Zambia. Evidence from molecular phylogenetic analyses using sequences rpb1, rpb2 and tef1α and morphological comparison support its placement in Afroboletus and it is distinct from the other related members of this genus in Africa. It is the first species with sequestrate basidiomata in the genus. A morphological description is augmented with line drawings and SEM images for the species.